Implementasi Metode UEQ dalam Analisis dan Evaluasi Aplikasi PERKASA (Perpustakaan Kabupaten Pamekasan) Berbasis Mobile - Tamara Adjuah; Rofiuddin Rofiuddin; Muslimah Qurniawati; Dimas Bagas Firmansyah Arifin (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2026)
The development of mobile-based digital library services is necessary to enhance information accessibility and improve the quality of library services. This community service activity aims to develop and evaluate the PERKASA application (Pamekasan Regency Library) as a mobile-based digital library service. The methods employed include direct observation and user experience evaluation using the User Experience Questionnaire (UEQ) and a four-point Likert scale questionnaire. The subjects of this activity were users of the PERKASA application at the M. Tabrani Regional Library of Pamekasan Regency, with a sample of 20 respondents. The research instruments were used to assess ease of use, effectiveness of the book search feature, clarity of information, application performance and stability, and interface design. Data were analyzed using a descriptive quantitative approach through percentage and mean score calculations. The evaluation results indicate that the PERKASA application received highly positive responses, with 100% of respondents agreeing or strongly agreeing on ease of use, clarity of information, and interface comfort. The effectiveness of the book search feature was also rated very positively, with 65% of respondents agreeing and 35% strongly agreeing. In terms of application performance and stability, 95% of respondents provided positive assessments, although a small number of users experienced minor technical issues. Based on these results, it can be concluded that the PERKASA application functions optimally as a mobile-based digital library information service and contributes to improving service quality and user experience.